ATIVIDADE DA ENZIMA E-NTPDase E PARÂMETROS HEMATOLÓGICOS EM PACIENTES JOVENS COM LEUCEMIA LINFOBLÁSTICA AGUDA - Flávia Castro Souto (2022)
Leukemias are hematological neoplasms that result from the clonal expansion of stem cells. The blood count is part of the routine investigation of a patient suspected of having leukemia. Leukemic cells proliferate disorderly in the bone marrow replacing normal hematopoietic cells, reflecting changes in the blood count. Studies show that patients with leukemia have changes in hematological parameters at diagnosis and also changes in the purinergic system. The purinergic system participates in several cellular functions, such as cell proliferation and cell death. E-NTPDase regulates the levels of ATP and ADP nucleotides that act as agonists for receptors that play an important role in tumor development and progression. In this context, the aim of this study was to evaluate the basic hematological parameters of peripheral blood, the activity of the E-NTPDase enzyme in bone marrow mononuclear cells and the membrane markers of young people with type B acute lymphoblastic leukemia. A total of 22 patients and divided into two groups: high risk (RA) and intermediate risk and low risk (RI/BR) of disease recurrence. The 22 patients had hematological parameters, number of leukocytes, hemoglobin content and number of platelets analyzed in the induction phase of treatment. E-NTPDase activity was analyzed in 11 patients at various stages of treatment and membrane markers, present in cell populations at diagnosis, were analyzed in 19 patients. Regarding the reference values of the blood count, the number of leukocytes, at diagnosis, of patients classified as RA was significantly high and patients in the RI/BR group also showed an increase, but closer to the limit of the reference value (10,000 /mm3). Such an increase is caused by the excessive proliferation of leukemic cells in the bone marrow that spreads to the peripheral blood presenting this alteration. This disordered proliferation of leukocytes decreases the production of erythrocytes and platelets. The two groups of patients in this study had, at diagnosis, low hemoglobin (Hb) and platelet numbers. The activity of E-NTPDase in the hydrolysis of ATP and ADP, in the cells of patients classified as RI/BR of disease recurrence, were higher compared to patients in the RA group. These findings differ from those found in the literature. Among the membrane markers present, three patients had a mutation in the CRLF2 gene. The results obtained in this study add to others found in the literature. Future experiments are needed to elucidate the profile of the purinergic system in patients with leukemias.